2020
DOI: 10.1073/pnas.1920474117
|View full text |Cite
|
Sign up to set email alerts
|

Active and repressed biosynthetic gene clusters have spatially distinct chromosome states

Abstract: While colocalization within a bacterial operon enables coexpression of the constituent genes, the mechanistic logic of clustering of nonhomologous monocistronic genes in eukaryotes is not immediately obvious. Biosynthetic gene clusters that encode pathways for specialized metabolites are an exception to the classical eukaryote rule of random gene location and provide paradigmatic exemplars with which to understand eukaryotic cluster dynamics and regulation. Here, using 3C, Hi-C, and Capture Hi-C (CHi-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 74 publications
(118 reference statements)
9
78
0
Order By: Relevance
“…Indeed, rapid responses involving one or several of the NUPs, KAKU4 and CRWN proteins have been reported during hyperosmotic stress (71), in response to copper in the medium (76) or upon biotic stress (77). Consistently, several examples suggest that gene expression in plants is influenced by the positioning of genes in respect to the nuclear periphery (76, 7880). As such, the nucleoskeleton may play a central role by recruiting specific chromatin domains at the nuclear periphery (21, 74).…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, rapid responses involving one or several of the NUPs, KAKU4 and CRWN proteins have been reported during hyperosmotic stress (71), in response to copper in the medium (76) or upon biotic stress (77). Consistently, several examples suggest that gene expression in plants is influenced by the positioning of genes in respect to the nuclear periphery (76, 7880). As such, the nucleoskeleton may play a central role by recruiting specific chromatin domains at the nuclear periphery (21, 74).…”
Section: Discussionmentioning
confidence: 73%
“…The scattered nature of metabolic gene clusters seems to be prevalent across plant genomes, as observed in the case of MIA gene clusters, as well as previously reported secondary metabolic gene clusters in other plant species 55 , 58 . With the complexities associated with the regulation of gene-expression in plants, it is only rational to suggest that physical proximity may not be sufficient to facilitate coexpression among genes within a gene cluster 57 . On the other hand, gene clusters represent discrete genome segments that serve as the hotspots for retaining and evolving specialized metabolite biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recently, CRWN1binding regions that are similar to NUP1-binding regions were also reported 26 . Silenced biosynthetic gene clusters approach the nuclear periphery, while activated clusters relocate away from it 37 . Other studies found that chromocenters are specifically localized at the nuclear periphery 38 .…”
Section: Discussionmentioning
confidence: 99%